Quadriceps Muscle Geometry and Strength Throughout Maturation in National-Level Male Soccer Players: A Cross-Sectional Study - Ritsche P; Roth R; Bernhard T; Nebiker L; Lichtenstein E; Franchi M; Spörri J; Faude O (Dove Medical Press, 2024)
Paul Ritsche,1 Ralf Roth,1 Thomas Bernhard,2 Lukas Nebiker,1 Eric Lichtenstein,1 Martino Franchi,3 Jörg Spörri,4,5 Oliver Faude1 1Department of Sport, Exercise and Health, University of Basel, Basel, Switzerland; 2FC Basel 1893, Basel, Switzerland; 3Human Neuromuscular Physiology Lab, Department of Biomedical Sciences, University of Padua, Padova, Italy; 4Sports Medical Research Group, Department of Orthopaedics, Balgrist University Hospital, University of Zurich, Zurich, Switzerland; 5University Centre for Prevention and Sports Medicine, Department of Orthopaedics, Balgrist University Hospital, University of Zurich, Zurich, SwitzerlandCorrespondence: Paul Ritsche, University of Basel, Department of Sport, Exercise and Health, Grosse Allee 6, Basel, 4052, Switzerland, Email Paul.ritsche@unibas.chPurpose: Adolescent soccer players experience distinct physiological changes due to chronological and biological maturation, impacting their soccer performance. Here, we explored age-related variations and associations between quadriceps geometry and strength in male national-level adolescent soccer players.Patients and Methods: We used ultrasonography to examine the regional architecture and morphology of the rectus femoris (RF) and vastus lateralis (VL) muscles, and we assessed knee extension strength by isometric and isokinetic dynamometry. Players were categorized into four age groups: under (U) 15 (n=18, age=13.7± 0.5 years), U16 (n=15, age=14.7± 0.5), U17 (n=19, age=15.7± 0.5), U18 (n=18, age=16.7± 0.5) and U21 (n=25, age=18.5± 0.5).Results: The absolute and relative strengths were higher in the U16 compared to U15 by 12- 15% and 6- 8%, 11- 12% and 6- 7% in the U17 compared to U16, 5- 7% and − 1- 2% in the U18 compared to U17 and 0- 15% and − 1- 11% in the U21 compared to U18 age groups, respectively. VL architecture did not change relevantly between the age groups. The muscle anatomical cross-sectional area (ACSA) of the VL and RF differed non-uniformly and muscle region-specific by 10- 36%, with highest values in the U21 age group. Moderate correlations between the VL architecture and knee extension strength in both legs were observed only in the U16 age group. The quadriceps ACSA showed age-specific correlations with knee extension strength.Conclusion: Our findings highlight non-uniform differences in quadriceps muscle morphology and absolute and relative strength among male national-level adolescent soccer players in different age groups. The correlations observed between muscle morphology or architecture and strength were muscle, muscle region, leg and age dependent.Keywords: strength, youth, muscle architecture, vastus lateralis, rectus femoris